The Development of a Training Model Based on Transformative Learning Concept and Self-esteem Theory to Enhance Service Mind of Airline Personnel - Vess, Romrudee (Scholar: Human Sciences, 2014)
This research was aimed to develop a training model for the airline personnel who are directly responsible for providing services to passengers such as cabin attendant, ground staff, reservation staff & ticketing staff (Front Line Staff). This research theory based on transformative learning concept and self-esteem theory and integrated by using non-formal education training model to develop a new training model in order to enhance service mind of the airline personnel that consisted of 3 main factors: a) Basic principles, b) Processes and c) Procedures.